The endosomal sorting complex required for transport repairs the membrane to delay cell death - Yang, Ye; Wang, Min; Zhang, Ying-Ying; Zhao, Shu-Zhi; Gu, Song (Frontiers in Oncology, 2022)
The endosomal sorting complex required for transport (ESCRT) machinery play a key role in the repair of damaged plasma membranes with puncta form and remove pores from the plasma membrane in regulated cell death, apoptosis, necroptosis, pyroptosis, ferroptosis and autophagy. ESCRT-I overexpression and ESCRT-III associated charged multivesicular body protein (CHMP) 4B participated in apoptosis, ESCRT-1 protein TSG 101 maintain low levels of ALIX and ALG-2, prevents predisposition to apoptosis. ESCRT-III components CHMP2A or CHMP4B are recruited to the broken membrane bubbles sites with the requirement of extracellular Ca2+, removed membrane vesicles from cells, delayed the time required for active MLKL to mediated necroptosis, thus preserving cell survival. CHMP4B disturbed pyroptosis by recruiting around the plasma membrane neck to remove the GSDMD pores and preserve plasma membrane integrity depending on Ca2+ influx. The accumulation of the ESCRT-III subunits CHMP5 and CHMP6 in the plasma membrane is increased by the classical ferroptosis activators erastin-1 and ras-selective lethal small molecule 3 (RSL3) upon cytosolic calcium influx concentration, and repair ferroptosis plasma membrane. ESCRT I-III also affected fusion between endosome and autophagosome accumulation to produce amphisomes, indicating ESCRT is a potential target to overcome drug resistance during tumor therapy.